Perencanaan Strategis Sarana dan Prasarana Pendidikan untuk Meningkatkan Efektivitas Layanan di Sekolah Dasar Islam: Sebuah Studi Kualitatif di Madrasah Ibtidaiyah MATLAUL ATFAL - Shinta Meirnawati Pratiwi Putri; Mulyawan Safwandy Nugraha (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the implementation of educational facilities and infrastructure planning to enhance service effectiveness at MI Matlaul Atfal. The research was driven by a gap between the ideal concept of needs-based facility planning and field practices that remain largely administrative. Using a descriptive qualitative approach, the study involved 6 participants, observations of 23 facility units, and an analysis of 12 documents related to procurement and inventory management. Data were analyzed through reduction, presentation, and conclusion drawing, supported by source triangulation. The findings indicate that structured planning, teacher involvement, and support from the school committee positively contribute to the availability of learning media, classroom comfort, and the smooth delivery of educational services. However, limited budgets, insufficient routine maintenance, and unequal distribution of facilities across classes remain major challenges. Theoretically, this study reinforces the significance of facilities planning in Islamic educational management, while practically it offers recommendations for optimizing procurement, maintenance, and continuous monitoring based on prioritized needs. Keywords: Educational Facilities Planning; Islamic Education Management; School Facilities Management; Service Effectiveness Abstrak Penelitian ini bertujuan menganalisis implementasi manajemen perencanaan sarana dan prasarana dalam meningkatkan efektivitas layanan pendidikan di MI Matlaul Atfal. Studi ini berangkat dari adanya kesenjangan antara konsep ideal perencanaan sarpras berbasis kebutuhan dan praktik lapangan yang masih bersifat administratif. Menggunakan pendekatan kualitatif deskriptif, penelitian melibatkan 6 partisipan, observasi terhadap 23 unit sarpras, serta analisis 12 dokumen terkait pengadaan dan inventarisasi. Data dianalisis melalui proses reduksi, penyajian, dan penarikan kesimpulan dengan triangulasi sumber. Hasil penelitian menunjukkan bahwa perencanaan sarpras yang terstruktur, pelibatan guru, dan dukungan komite sekolah berkontribusi positif terhadap ketersediaan media pembelajaran, kenyamanan ruang kelas, dan kelancaran layanan pendidikan. Namun, keterbatasan anggaran, kurangnya perawatan berkala, dan ketimpangan distribusi sarpras masih menjadi hambatan utama. Secara teoritis, penelitian ini memperkuat pentingnya perencanaan sarpras dalam manajemen pendidikan Islam, sementara secara praktis memberikan rekomendasi untuk optimalisasi pengadaan, perawatan, dan monitoring berbasis prioritas. KATA KUNCI: Efektivitas layanan; Manajemen pendidikan Islam; Pengelolaan fasilitas sekolah; Perencanaan sarana prasarana.